2013
DOI: 10.1103/physreva.87.063619
|View full text |Cite
|
Sign up to set email alerts
|

Outcoupling vector solitons from a Bose-Einstein condensate with time-dependent interatomic forces

Abstract: We discuss the possibility of emitting vector solitons from a two-component elongated BEC by manipulating in time the inter-or intraspecies scattering lengths with Feshbach resonance tuning. We present different situations which do not have an analog in the single species case. In particular, we show vector soliton outcoupling by tuning the interspecies forces, how the evolution in one species is controlled by tuning the dynamics of the other, and how one can implement the so-called supersolitons. The analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…We note at this point, that the coupled nonlinear Schrödinger equations considered in this work, may be physically related to coupled nonlinear waveguide arrays [63] as well as two-species Bose-Einstein condestates [64,65,66]. These MI results, together with those obtained in [51], open many opportunities for future research directions.…”
Section: Discussionmentioning
confidence: 54%
“…We note at this point, that the coupled nonlinear Schrödinger equations considered in this work, may be physically related to coupled nonlinear waveguide arrays [63] as well as two-species Bose-Einstein condestates [64,65,66]. These MI results, together with those obtained in [51], open many opportunities for future research directions.…”
Section: Discussionmentioning
confidence: 54%
“…Taking this into regard, we here address a novel system of coupled NLS-type equations, including the SPM, XPM, and FWM terms with a time-dependent coefficient, and a time-dependent antitrapping parabolic potential. The equations are written in the notation corresponding to BEC models based on Gross-Pitaevskii (GP) equations [22,23]:…”
Section: The Modelmentioning
confidence: 99%
“…The dynamics of multicomponent solitons is described by systems of coupled nonlinear Schrödinger (NLS) equations [see, e.g., recent works [8]- [10], and very recent ones [11]- [17] dealing with two-component solitons in spin-orbit-coupled Bose-Einstein condensates (BECs)]. In particular, the concept of energy sharing in the Manakov model [18], or in the modified version of this model [19] governed by coupled NLS equations [20], was a catalyst for looking for new integrable models in nonlinear optics [21], BECs [22,23], metamaterials [24,25], etc. It was found that, in all available integrable systems of two coupled NLS-type equations, the ratio between the self-phase-modulation (SPM) and cross-phase-modulation (XPM) coefficients, which account for the interaction of the components with themselves or with each other, are equal, while physically realistic systems depart from this constraint.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of BEC solitons in the harmonic-lattice potentials has become a hot research topic both in theory [11][12][13] and experiment [14,15]. Some more recent accounts have been presented in [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%